2015
DOI: 10.1002/cjp2.18
|View full text |Cite
|
Sign up to set email alerts
|

In‐depth molecular profiling of the biphasic components of uterine carcinosarcomas

Abstract: Uterine carcinosarcoma is a clinically aggressive malignancy composed of a mix of carcinomatous and sarcomatous elements. We performed targeted next‐generation sequencing of 27 uterine cancer and sarcoma genes together with immunohistochemical analyses of selected proteins in 30 uterine carcinosarcomas. This included 13 cases in which the distinct carcinoma and sarcoma components were sequenced separately and 10 cases where the metastatic tumours were analysed in addition to the primary tumours. We identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
80
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(106 citation statements)
references
References 39 publications
(55 reference statements)
15
80
1
1
Order By: Relevance
“…The mutations that we discovered in this study were reminiscent of what was reported in the far more common endometrial carcinomas. In addition, molecular features including DNA methylation, copy number and gene expression recapitulate the endometrial versus serous dichotomy observed in endometrial carcinomas, which was in line with a previous report studying genetic mutation (McConechy et al, 2015). This paper also identified concordant mutation profiles in microdissected carcinoma and sarcomatous components of primary tumors as well as between primary and metastatic lesions.…”
Section: Discussionsupporting
confidence: 89%
“…The mutations that we discovered in this study were reminiscent of what was reported in the far more common endometrial carcinomas. In addition, molecular features including DNA methylation, copy number and gene expression recapitulate the endometrial versus serous dichotomy observed in endometrial carcinomas, which was in line with a previous report studying genetic mutation (McConechy et al, 2015). This paper also identified concordant mutation profiles in microdissected carcinoma and sarcomatous components of primary tumors as well as between primary and metastatic lesions.…”
Section: Discussionsupporting
confidence: 89%
“…In an earlier report, using a targeted sequencing approach to study the biphasic nature of uterine carcinosarcoma, we found identical mutations and similar mutational burdens in matched carcinoma and sarcoma components, consistent with a clonal relationship 2. Since uterine carcinosarcomas are essentially metaplastic high‐grade carcinomas, it may be reasonable to speculate that CNAs may be more prevalent than point mutations, based on extrapolation of the genomic profiling data from high‐grade serous carcinoma 4, 5.…”
Section: Discussionsupporting
confidence: 67%
“…Molecular studies that analyzed the carcinoma and sarcoma components of individual tumors separately found evidence of shared alterations between each component in a majority of cases . Thus, the majority of UCSs are believed to be monoclonal in origin, resulting from a metaplastic transition of carcinoma cells to sarcoma cells .…”
Section: Introductionmentioning
confidence: 99%